Analysis of Exchange Rates and Food Security of Small Fisher Households (Case Study of Medang Island, Sumbawa Regency) - Husni, Syarif (Jurnal Biologi Tropis, 2024)
The basic problem faced by fishing households, especially small fishing households, is the uncertain level of income to meet household needs, both food and non-food. Therefore, the level of income and expenditure of small fishing households influences the fishermen's exchange rate, food consumption patterns and the level of food security of fishing households. The research objectives are 1) to analyze the income and expenditure of small-scale fishing households, 2) to analyze the Fisherman's Exchange Rate (FER), and 3) to analyze the level of food security of small-scale fishing households on Medang Island. Data collection uses survey techniques and uses case studies. 40 small fishing households were selected using Quota Sampling. Next, the determination of respondents was carried out using Simple Random Sampling. The household income of fishermen on Medang Island is IDR 73,643,157 per year, sourced from on-fishing, IDR 65,952,248, non-fishing, IDR 7,090,910, and other sources IDR 600,000 per year. Fisherman household expenditure on Medang Island is IDR 43,270,909 including food expenditure IDR 17,044,364 and non-food IDR 26,226,545 per year. An FER of 1.7 means that small fishing households have a level of welfare sufficient to meet primary needs and can potentially meet non-primary needs or save. In general, small fishing households on Medang Island are categorized as "food secure" households, but if disaggregated by household, 75% are food secure and 25% are food insecure (food insecure).